O SERVIÇO SOCIAL E AS TRAMAS DO FETICHE DO DESENVOLVIMENTO SUSTENTÁVEL NA PARTICULARIDADE DO SETOR ELÉTRICO NA AMAZÔNIA LEGAL: “velhas” e “novas” demandas profissionais. - BERGER, Mariana Cavalcanti Braz (2018)
This work analyses the texture of the sustainable development as a fetish considering the electrical sector in the Amazon. Address its importance for the capitalist development project and its relationship with different dimensions of the Social Work: professional education, knowledge production, political organization and professional intervention, through the old and new demands for the profession and the social workers that cope with the environmental issue. What is fundamental due to the current worsening of the social issues. This thesis employs the method and critical theory of Marx and marxism, it uses bibliographic research; documental research, specially to understand the particularity of the hydroelectric power units; interviews with people affected by the dams and with social workers that acts in the sector. Besides that, the research comprises also the application of questionnaires for the coordinators of social work undergraduate courses in the Amazon region and representatives of the professional bodies. In this way, it is possible to uncover the fetish of the environmental development in the power generation industry of Brazil, despite the fact its main actors claim to be engaged with the environmental preservation. That is an absurdity, as these large projects destroy the habitats, flood people life and causes unrecoverable changes for the native population. It is due to the mechanism of capitalist, which appropriates riches to deliver goods. This reality challenges the social worker through old and new demands. It is observed that as the social work confronts the environment destruction, new demands arise regarding all professional dimensions. The addressment of the sustainable development and of the environmental issues by the professional education, knowledge production and political organization dimensions encourages the ideological resistance to the conservatism in the political-theoretical field. However, the reality is contradictory, there are the dilemmas with respect to the professional intervention and the ethical-political project, fundamentally connected to the interest of the workers class. The unveiling of the fetish of the sustainable development contributes to disrupt the productivist logic, that argues is possible to conciliates the habitat preservation and the world market demand, through a system controlled by greed and profit. The Marxist critical view, so developed by the Social Work, is faced by the conservatism and deep drawbacks concerning social relations. Theses drawbacks must be confronted through the reinforcement of ethical-political project.